IMPACT OF THE PSYCHOLOGICAL FACTOR ON THE ORGANIZATION OF THE ECONOMIC SECURITY OF BUSINESS ACTIVITIES - Воронюк, Євгенія Валеріївна; Сатушева, Карина В. (Journal of Strategic Economic Research, 2023)
Economic security of business activity, especially in the conditions of political and economic instability, faced by the world economy, appears to be an important component of successful business. In today’s world, when the range of threats and risks to the economic security of business activity is constantly expanding and updating, a large number of business entities continue to provide for the current needs of the enterprise without using all the advantages provided by the effective organizational provision of economic security of business activity. This situation in the field of entrepreneurship is connected with many factors. However, even taking into account the speed of development of information technologies, the constant increase in the amount of information, the creation and development of new communication systems, the increase in the level of competition in various sectors of the economy, the psychological factor of the organization of economic security of entrepreneurial activity plays a key role for business, since these functions are performed by people. The psychological characteristics of employees who, according to their functional duties, are responsible for the organization of economic security of entrepreneurial activity, affect the quality and efficiency of the created system. The development of the subject of entrepreneurial activity, the construction of effective communication systems, the development and use of measures to reduce or avoid risks depend on them. It follows that the workload of the employee, working conditions, the quality of the corporate culture and the management style directly affect the efficiency of the employees and their psychological state. Such a situation demonstrates the need for each enterprise to take into account the peculiarities of the psychological factor during the development and implementation of organizational support for the economic security of entrepreneurial activity. The stability of the operation of the enterprise lies in the efficiency of the organized system of economic security of the business, which prevents or reduces the level of negative influence of various factors, both external and internal. The goal of every enterprise is to achieve economic benefit, increase profit from its activity. A modern enterprise, regardless of the sphere of activity and scale of business, is a specific socio-economic system, the key element of its functioning is its resource potential. However, it should be emphasized that the human factor dominates all other types of enterprise resources in the wide list of enterprise resource provision. In this aspect, the study of the psychological factor of organizational provision of economic security of entrepreneurial activity becomes necessary for increasing business profits.